Guillain-Barré syndrome after surgery: a literature review - Li, Xiaowen; Zhang, Chao (Frontiers in Neurology, 2024)
Guillain-Barré syndrome (GBS) is a rare postoperative complication that is sometimes characterized by serious motor weakness and prolonged weaning from mechanical ventilation. Although the exact nature of the relationship between GBS and the surgical procedure is still unclear, there is a clear increased incidence of GBS in post-surgical patients compared to non-surgical patients. GBS after surgery is unique in several ways. The course of post-surgical GBS unfolds more rapidly than in other situations where GBS develops, the condition is often more severe, and respiratory muscles are more commonly involved. Prompt diagnosis and appropriate treatment are essential, and the condition can worsen if treated inappropriately. Postoperative sedation, intubation, and restraint use make the diagnosis of GBS difficult, as the onset of symptoms of weakness or numbness in those contexts are not obvious. GBS is often misdiagnosed, being attributed to other postoperative complications, and subsequently mishandled. The lack of relevant information further obscures the clinical picture. We sought to better understand post-surgical GBS by performing an analysis of the relevant literature, focusing on clearly documenting the clinical characteristics, diagnosis, and management of GBS that emerges following surgery. We underscore the importance of physicians being aware of the possibility of GBS after major surgery and of performing a variety of laboratory clinical investigations early on in suspected cases.